`g(t) = (3t^2 - 1)/(2t + 5)` Use the Quotient Rule to find the derivative of the function.

Textbook Question

Chapter 2, 2.3 - Problem 8 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

`g(t) = (3t^2 - 1)/(2t + 5)`

`g'(t) = [(2t+5)*(6t) - (3t^2 - 1)*2]/(2t+5)^2`

`g'(t) = [12t^2 + 30t - 6t^2 + 2]/(2t+5)^2`

`or, g'(t) = (6t^2 + 30t + 2)/(2t+5)^2`

``

` `

We’ve answered 318,989 questions. We can answer yours, too.

Ask a question